Tumor necrosis factor α-converting enzyme mediates MUC5AC mucin expression in cultured human airway epithelial cells - Shao, Matt X. G. (National Academy of Sciences, 2003)
Ectodomain shedding of epidermal growth factor receptor (EGFR) ligands [e.g., transforming growth factor type α (TGF-α)] and EGFR phosphorylation are implicated in mucin production in airway epithelial cells. Tumor necrosis factor α-converting enzyme (TACE) is reported to cleave precursor of TGF-α, with release of soluble mature TGF-α in various epithelial tissues. We hypothesized that TACE increases the shedding of TGF-α, resulting in EGFR phosphorylation and inducing mucin production in human airway epithelial (NCI-H292) cells. To examine this hypothesis, we stimulated NCI-H292 cells with phorbol 12-myristate 13-acetate (PMA, an activator of TACE) and pathophysiologic stimuli [lipopolysaccharide (LPS) and supernatant from the Gram-negative bacterium Pseudomonas aeruginosa (PA sup)]. PMA, PA sup, and LPS increased MUC5AC gene expression and mucin protein production, effects that were prevented by pretreatment with AG1478, a selective inhibitor of EGFR phosphorylation and by preincubation with an EGFR-neutralizing Ab or with a TGF-α-neutralizing Ab, implicating ligand (TGF-α)-dependent EGFR phosphorylation in mucin production. These stimuli induced release of soluble TGF-α, EGFR phosphorylation, and MUC5AC expression, which were blocked by the metalloprotease inhibitors tumor necrosis factor-α protease inhibitor-1 and tissue inhibitor of metalloprotease-3. We specifically knocked down the expression of metalloprotease TACE by using small interfering RNA for TACE. Knockdown of TACE inhibited PMA-, PA sup-, and LPS-induced TGF-α shedding, EGFR phosphorylation, and mucin production. From these results, we conclude that TACE plays a critical role in mucin production by airway epithelial cells by means of a TACE ligand–EGFR cascade in response to various stimuli.